2016
DOI: 10.1093/humupd/dmw023
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroid management: from the present to the future

Abstract: Uterine fibroids (also known as leiomyomas or myomas) are the most common form of benign uterine tumors. Clinical presentations include abnormal bleeding, pelvic masses, pelvic pain, infertility, bulk symptoms and obstetric complications.Almost a third of women with leiomyomas will request treatment due to symptoms. Current management strategies mainly involve surgical interventions, but the choice of treatment is guided by patient's age and desire to preserve fertility or avoid ‘radical’ surgery such as hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
506
0
31

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 538 publications
(579 citation statements)
references
References 223 publications
5
506
0
31
Order By: Relevance
“…Uterine myomas are the most commonly found benign tumors in women of reproductive age and they can cause abnormal uterine bleeding, pelvic pressure and pain, and reproductive dysfunction [1, 2]. Progesterone is particularly essential to myoma development [3] with myomas exhibiting higher progesterone receptor (PR) levels compared with adjacent myometrium [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…Uterine myomas are the most commonly found benign tumors in women of reproductive age and they can cause abnormal uterine bleeding, pelvic pressure and pain, and reproductive dysfunction [1, 2]. Progesterone is particularly essential to myoma development [3] with myomas exhibiting higher progesterone receptor (PR) levels compared with adjacent myometrium [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, UPA was approved for this purpose as it showed comparable efficacy to leuprolide acetate with fewer side effects. 5,6 Moreover, it has been reported that the reduction in fibroid size is maintained for at least six months after the treatment. 5 Most of medical alternatives available for fibroids management have limitations: when it comes to fertility some prevent conception whereas others have little information regarding its effects on a future pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, it reduces fibroids and uterine volume, and it is sustained for at least six months after treatment. 5,6 Although there is still few evidence concerning UPA and pregnancy, no adverse effects were reported so far, making it an option for women who desire to conceive in the short-term.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 Other less common symptoms include pelvic pressure, vaginal bleeding, urinary frequency, and constipation. 7,10 The large-sized fibroids exert pressure effects on nearby organs as well. Anterior cervical fibroids compress the urinary bladder leading to frequent micturition.…”
Section: Diagnosis Of Uterine Fibroids Among Pregnancymentioning
confidence: 99%